Penerapan Metode RCM II untuk Meningkatkan Performa pada Strainer - Candra Apriyanto Sanjaya; George Endri Kusuma; Mohamad Hakam (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Missile Fast Boat (KCR 60M) with the type of patrol boat and Hospital Assistance Ship (BRS). In some maintenance processes carried out on the ship system, counted on average carried out for 2 weeks. But that is done for all different equipment and machinery. The topic taken was performance analysis and maintenance proposals for the strainer. Strainer is a support component that functions as an outside water filter that will enter the ship system, because the strainer is the initial entrance of water and easy to do checks and can extend the life time of components such as pumps and heat exchangers that exist in the system. And to analyze all of these things use the Failure Mode and Effect Analysis (FMEA) and Realibility Centered Maintenance (RCM) methods and the data used such as TTF (Time to Failure) and TTR (Time to Repair). The application of this method is obtained the right maintenance time and more effective. The application of this method to each system on the ship is a sea chest system, sea water cooler system, ballast system, getting an additional maintenance time of 88 hours or about 3 days for the maintenance deadline. In the fuel oil transfer & purifying system, the maximum maintenance time limit is 982 hours or 40 days. As for the oil fill & transfer system to get results which is a time difference of 4.208 hours or about 5 months earlier than company data, it can be a suitable scheduling proposal for each of these systems. And the maximum fouling factor for the strainer component is 3.21 mm. As a result, the life time possessed by each machine component will be longer and its performance becomes optimal especially for strainer components that don’t have a fixed maintenance schedule.